2023
DOI: 10.1021/acssuschemeng.3c04920
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Coordination of Neodymium in Ionic Liquid: Insights to Guide Sustainable Recovery

Garima S. Dobhal,
Le Nhan Pham,
Sherif Abdulkader Tawfik
et al.

Abstract: Neodymium is a critical metal essential for advancing sustainable clean energy technologies, as it is a crucial component in the manufacturing of NdFeB permanent magnets, part of wind turbines, electric vehicles, and advanced electronics. Its recovery from secondary sources using electrochemical deposition in ionic liquids has the potential to sustainably achieve a closed-loop alternative to obtain the metal. The presence of water in low, specific concentrations in ionic liquid has been previously shown to cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…A water content of 0.4 wt% enhanced neodymium reduction by the reorganization of the coordination environment of the metal ion by means of a varied cis / trans coordination ratio, with [NTf 2 ] − rather acting as a monodentate ligand and partial [NTf 2 ] − replacement. 86,87…”
Section: Ionometallurgymentioning
confidence: 99%
“…A water content of 0.4 wt% enhanced neodymium reduction by the reorganization of the coordination environment of the metal ion by means of a varied cis / trans coordination ratio, with [NTf 2 ] − rather acting as a monodentate ligand and partial [NTf 2 ] − replacement. 86,87…”
Section: Ionometallurgymentioning
confidence: 99%
“…It was shown that the electrodeposition of Nd(III) in ionic liquids media is dependent of the presence of water in the system. In fact, the presence of water catalyzed the electrodeposition of the rare earth, thus, the introduction of water into the coordination sphere of the complex formed by this REE and bis(trifluoromethanesulfonyl)imide [NTf2 -] anions and its influence on the metal deposition was investigated [27]. The addition of water produced various effects in the Nd 3+ [NTf2 -] complexes affecting the Nd 3+ electrochemical reduction, these effects can be summarized as: cis/trans transformation of the anion, change from bidentate to monodentate forms in the coordination mode of the anion and preferably coordination of water with the transition metal.…”
Section: Electrodepositionmentioning
confidence: 99%